Study of clinical presentation of malaria and the associated liver profile changes in various species of plasmodia - Biradar, Siddanagouda M.; Holyachi, Renuka (International Journal of Research in Medical Sciences, 2016)
Background: Malaria is one of the most common widespread infectious diseases in the tropical developing countries. It affects nearly 300-500 million cases every year with a mortality rate of 1.2-2.7 million deaths per year. Objectives of the study were to study the clinical presentation and liver profile changes in acute malaria caused by various plasmodium species. Medical college and Research centre, Bijapur, Karnataka, India. Methods: One hundred subjects with peripheral smear positive for malarial parasite were included in the study. The alterations in liver profile laboratory parameters were determined in various plasmodium species and reported. Results: Of 100 patients, 44 were Plasmodium falciparum (Pf), 51 were Plasmodium vivax (Pv) and 5 were mixed (Pf + Pv) infection. Fever (97%), chills (83.2%) and sweating (73.26) were the predominant presenting symptoms. Splenomegaly was detected in 78-80% individuals. Jaundice was more common in P. falciparum and mixed infection as compared to P. vivax. Conclusions: Malaria is a potential cause of morbidity and mortality in the tropical countries. Jaundice is one of the common presentations of falciparum malaria. The raised serum bilirubin could be due to both hemolysis and hepatocellular dysfunction. Early diagnosis and treatment will help in reducing further complications like severe anaemia, hepatic encephalopathy, acute renal failure and disseminated intravascular coagulation.